Antimalarial Efficacy and Antioxidant Activity of Lophira lanceolata Stem Bark Ethanol Extract Using Plasmodium berghei Induced-Malaria in Swiss Albino’s Mice - Mounvera Abdel Azizi; Noumedem Anangmo Christelle Nadia; Yamssi Cedric; Ngouyamsa Nsapkain Aboubakar Sidiki; Gamago Nkadeu Guy-Armand; Djeussi Doriane Esther; Tientcheu Noutong Jemimah Sandra; Tako Djimefo Alex Kevin; Vincent Khan Payne (Journal of Parasitology Research)
Background. Malaria remains a major public health problem in the tropical and subtropical regions. This study aimed of investigating the antimalarial and antioxidant activities of ethanol extract of Lophira lanceolata stem bark. Methodology. The antimalarial activity was determined using the Peter 4-days’ suppressive and Rane’s curative tests on Swiss albino: these mice were infected with 1×107 parasitized red blood cells. The percentage reduction of parasitemia was related to each test, and the liver homogenate was used to assay malondialdehyde, superoxide dismutase, nitrogen monoxide, catalase, and glutathione for the evaluation of oxidative stress. During the curative test, blood was collected for hematological parameters, alanine aminotransferase and aspartate aminotransferase to evaluate liver function. Result. The ethanol extract of L. lanceolata showed a dose-dependent suppressive activity with the highest suppression of 88.22% at 500 mg/kg. Suppression produced by the extract was not significantly higher than that of the reference drug with 96.1%. Similarly, the extract at doses 125, 250, and 500 mg/kg showed significant decreases (P<0.05) in a dose-dependent manner during the curative test. The ethanol extract of L. lanceolata caused a reduction of tissue markers, such as hepatic oxidative stress, as it increased the enzymatic activity of antioxidant enzymes. Conclusion. The ethanol extract of L. lanceolata possesses both antimalarial and antioxidant activities. However, further in vivo toxicity tests are required to guarantee their safety.